A questão da mobilidade urbana: o estudo de caso do centro da cidade de Rio Claro-SP - Zaguini, Juliana Corrêa [UNESP] (2014)
The development of medium-sized cities in recent decade, caused, partly, by the industrial deconcentration process generated, beyond benefits, several problems for these cities population. The unplanned rapid growth of these cities, together with the capitalist model of production collaborated for the increase of socioeconomics questions in these locations. The urban mobility became one of these problems, embarrassing citizen's lives, especially in downtown area. Therefore, the State began looking for solutions to improve urban mobility of the population, contributing to their quality of life and also to adapt the city to new market demand. Moreover, it is a function of the government enable of urban mobility policy fits the needs of society, since practically all city dwellers depend on the activity of dislocation. In these work, we analyzed the situation of Brazilian medium-sized cities downtown area, as well as its growth process, tanking as an example the case of the city of Rio Claro - SP. Seeks to understand the problems created by the growth of medium-sized cities in recent decades, and also analyze the performance of proposed projects by government